2010
DOI: 10.1007/s11105-010-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of SSR and AFLP Markers for Evaluation of Genetic Diversity and Conservation of Fig, Ficus carica L., Genetic Resources in Tunisia

Abstract: This study characterises the genetic variability of fig, Ficus carica L., using simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers. It compares the efficiency and utility of the two techniques in detecting variation and establishing genetic relationships among Tunisian fig cultivars.Our results show that using both marker systems, the Tunisian fig germ plasm is characterised by having a large genetic diversity at the deoxyribonucleic acid level, as most of AFLP bands were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 39 publications
5
31
5
Order By: Relevance
“…For the remaining genotypes, the genetic distance matrix showed a high level of divergence at the DNA level. Similar result was reported by Baraket [32].…”
Section: Discussionsupporting
confidence: 92%
“…For the remaining genotypes, the genetic distance matrix showed a high level of divergence at the DNA level. Similar result was reported by Baraket [32].…”
Section: Discussionsupporting
confidence: 92%
“…Pomological and morphological traits as well as molecular markers were used to analyse genetic diversity and characterize local cultivars [8,[13][14][15][16][17][18][19]. Recently, …”
Section: Introductionmentioning
confidence: 99%
“…With only five primers, it was possible to discriminate among all landraces studied, identifying 103 alleles and 155 different genotypes. In fig (F. carica L.), six SSR primers permitted to discriminate among 72 Tunisian local varieties with a resolving power of 97.2% (Saddoud et al, 2007;Baraket et al, 2010), the tested primers revealed 58 alleles and 124 genotypes. An identification key for 26 Tunisian olives (Olea europaea L.) was successful established for discriminating among local cultivars using three of ten SSR markers by Taamalli et al (2008).…”
Section: Gs1 Gs1mentioning
confidence: 99%